2003
DOI: 10.1099/ijs.0.02600-0
|View full text |Cite
|
Sign up to set email alerts
|

Tepidibacter thalassicus gen. nov., sp. nov., a novel moderately thermophilic, anaerobic, fermentative bacterium from a deep-sea hydrothermal vent

Abstract: Tepidibacter thalassicus gen. nov., sp. nov., a novel moderately thermophilic, anaerobic, fermentative bacterium from a deep-sea hydrothermal vent Micro-organisms inhabiting deep-sea hydrothermal vents are physiologically and phylogenetically diverse, and are represented by members of the Bacteria and the Archaea (Jeanthon, 2000). Chemo-organotrophic thermophilic anaerobic bacteria isolated from these extreme environments include members of the order Thermotogales -Thermosipho melanesiensis ( et al., 2002b). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…They fermented peptone and glucose into propionate and butyrate. Strain UXO3‐5, a typical strain of group III bacteria, was closely related to the two recognized species Tepidibacter thalassicus DSM 15285 T (Slobodkin et al , 2003) and Tepidibacter formicigens DSM 15518 T (Urios et al , 2004), with 96.8−97.3% similarity in their 16S rRNA gene (Fig. 1).…”
Section: Resultsmentioning
confidence: 94%
“…They fermented peptone and glucose into propionate and butyrate. Strain UXO3‐5, a typical strain of group III bacteria, was closely related to the two recognized species Tepidibacter thalassicus DSM 15285 T (Slobodkin et al , 2003) and Tepidibacter formicigens DSM 15518 T (Urios et al , 2004), with 96.8−97.3% similarity in their 16S rRNA gene (Fig. 1).…”
Section: Resultsmentioning
confidence: 94%
“…The presence of sequence reads from bacterial taxa Tepidibacter sp., Ignavibacterium sp., Teribacillus sp., Dechloromonas sp., could be the representatives of novel species within these genera. The genus Tepidibacter ( Firmicutes ) was proposed (Slobodkin et al 2003) with three reported type species i.e. Tepidibacter thalassicus, Tepidibacter formicigenes and Tepidibacter mesophilus (Tan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Considering these limitations, we have isolated glucose-, xylose-, or glycerol-fermenting bacteria from the extreme deep biosphere environment of the former Homestake gold mine, Lead, SD. There are very few reports on subsurface isolates utilizing glucose for ethanol production (Alain et al, 2002; Slobodkin et al, 2003; Slobodkina et al, 2008) but the information on xylose and glycerol fermenting deep subsurface microbes is relatively scarce. Deep subsurface microbes, Tepidibacter thalassicus and Clostridium tepidiprofundi sp.…”
Section: Introductionmentioning
confidence: 99%
“…Deep subsurface microbes, Tepidibacter thalassicus and Clostridium tepidiprofundi sp. nov., fermented glucose into ethanol, acetate, and H 2 (Slobodkin et al, 2003; Slobodkina et al, 2008). Another strain, Caminicella sporogenes gen. nov., sp.…”
Section: Introductionmentioning
confidence: 99%